A durable and impact-resistant PETG heat shrinkable film and a preparation method thereof

By adopting a three-layer structure durable and bump-resistant PETG heat shrink film, the existing PETG heat shrink film is easily afflicted and bumped during transportation and use, and the film is improved by improving the resistance to bumps, scratch resistance and printing, extending its service life and maintaining the aesthetics of the packaging.

CN116001403BActive Publication Date: 2025-03-14HENAN DAXINYUAN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211556487.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-06
Publication Date
2025-03-14
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

The existing PETG heat shrink film is easily worn and bumped during transportation and use, resulting in brittle breakage, scratches, damage and even breakage of the film, seriously affecting the packaging effect and service life.

Method used

A durable and bump-resistant PETG heat shrink film with a three-layer structure includes a printing layer, a core layer and a durable layer. The printing layer is mainly composed of NPG modified PET and functional masterbatch. The core layer contains PET, PETG and bump-resistant toughening agent. The durable layer contains NPG modified PET, PET, scratch resistant agent, functional masterbatch and lubricant. Through specific layer ratios and process processing, the film is improved to resist bumps, scratches and printing.

Benefits of technology

It effectively reduces scratches and bumps caused by the film during transportation and use, improves the overall bump resistance and printing properties of the film, extends the service life, and maintains the aesthetics of the packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003983552780000111
    Figure BDA0003983552780000111
Patent Text Reader

Abstract

The present invention discloses a durable and bump-resistant PETG heat shrinkable film, which comprises a printing layer, a core layer and a durable layer in sequence, wherein the printing layer mainly comprises NPG-modified PET and a functional masterbatch; the core layer mainly comprises PET, PETG and a bump-resistant toughening agent; the durable layer mainly comprises NPG-modified PET, PET, a scratch-resistant agent, a functional masterbatch and a lubricant; the present invention also discloses a method for preparing the above-mentioned heat shrinkable film, wherein the raw materials of each layer are dried and uniformly mixed, and the heat shrinkable film is obtained through extrusion, melt plasticization, die casting, biaxial stretching, cooling and shaping, and winding. The heat shrinkable film prepared by the method of the present invention has a three-functional layer structure, and the film as a whole can integrate the advantages of each functional layer. At the same time, the materials of each layer are derivatives of PET materials, with similar polarity, and there is no problem of stratification, which can reduce the difficulty of equipment operation, reduce the process flow, and reduce the overall thickness of the film, thereby reducing the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat shrinkable films, and in particular relates to a durable and impact-resistant PETG heat shrinkable film and a preparation method thereof. Background Art

[0002] As an environmentally friendly polyester film, PETG heat shrink film has good mechanical strength, barrier properties, chemical stability and environmental affinity. It is widely used in beverage packaging, daily chemical packaging and battery packaging. However, most PETG heat shrink labels on the market will suffer from wear and collision during transportation and use, and will break during printing, closing or sleeve labeling, which seriously affects the normal printing and closing of the back end of the film. After the label sleeve is used on the container, there will be collision and friction between the bottles and between the bottles and the packaging box during transportation. Due to the poor collision resistance of the label, the label surface will be scratched, damaged or even broken after a long period of transportation, which will seriously affect the packaging effect and cause great losses.

[0003] For many packaging situations, the wear resistance of the label can be increased by using wear-resistant and scratch-resistant inks, but the bumps on the edges of the packaging container will directly damage the label film and cause the film to break. Therefore, improving the film's own bump resistance from the source can effectively reduce the damage to the label film during transportation.

[0004] The methods reported in the literature to increase the film's anti-collision performance are to add wear-resistant ink and coating or to compound with other materials, etc. However, the use of wear-resistant ink and coating cannot fundamentally solve the problem of label damage, and after the PETG film is compounded with other materials, the material strength is increased but the overall material does not shrink, resulting in the problem that the sleeve label cannot shrink. Summary of the invention

[0005] In view of the defects and shortcomings of the prior art, the present invention provides a durable and impact-resistant PETG heat shrinkable film and a preparation method thereof. The heat shrinkable film prepared by the present invention can effectively reduce scratches and dents caused by the film in long-distance transportation and contact with other objects during use, thereby improving the film's own impact resistance from the root.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a durable and impact-resistant PETG heat shrinkable film, which comprises a printing layer, a core layer and a durable layer in sequence; the printing layer mainly comprises NPG-modified PET and a functional masterbatch; the core layer mainly comprises PET, PETG and an impact-resistant toughening agent; the durable layer mainly comprises NPG-modified PET, PET, a scratch-resistant agent, a functional masterbatch and a lubricant. The mass percentage of NPG modified PET in the printing layer is 96.0% to 99.2%, and the mass percentage of functional masterbatch is 0.8% to 4.0%; the mass percentage of PETG in the core layer is 60% to 75%, the mass percentage of anti-collision toughening agent is 5% to 15%, and the mass percentage of PET is 10% to 35%; the mass percentage of NPG modified PET in the durable layer is 72.5% to 85.5%, the mass percentage of PET is 10% to 15%, the mass percentage of the anti-scratch agent is 1.5% to 2.5%, the mass percentage of functional masterbatch is 0.8% to 4.0%, and the mass percentage of lubricant is 2.2% to 6.0%.

[0007] Preferably, the PETG is S2012, Eastman GN071 or Eastman 0603.

[0008] Preferably, the PET is Sinopec Yizheng Chemical Fiber BG80, Sinopec Yizheng Chemical Fiber FG600 or Yuanhong Polymer YH600.

[0009] Furthermore, the scratch-resistant agent is transparent powder, nano zinc oxide or nano calcium carbonate.

[0010] Preferably, the functional masterbatch is compounded with erucamide and one or more of silicon dioxide, talc, clay, and kaolin.

[0011] Furthermore, the anti-collision toughening agent is POE-g-GMA (glycidyl methacrylate grafted polypropylene elastomer) or E-MA-GMA (terpolymer containing glycidyl methacrylate).

[0012] Furthermore, the lubricant is one or more of oleamide, erucamide, stearyl alcohol, pentaerythritol, and pentaerythritol stearate.

[0013] Preferably, the durable and impact-resistant PETG heat shrinkable film has a thickness of 30 to 100 μm.

[0014] Preferably, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0015] A method for preparing the above-mentioned durable and impact-resistant PETG heat shrinkable film comprises the following steps:

[0016] Step (1), drying the raw materials in a vacuum dryer to remove moisture;

[0017] Step (2), preliminarily mixing NPG modified PET and functional masterbatch in a mixer at a ratio of 96.0% to 99.2% and 0.8% to 4.0% by mass as a mixed raw material for the printing layer; preliminarily mixing PETG, a knock-resistant toughening agent and PET in a mixer at a ratio of 60% to 75%, 5% to 15% and 10% to 35% by mass as a mixed raw material for the core layer; preliminarily mixing NPG modified PET, PET, a scratch-resistant agent, a functional masterbatch and a lubricant in a mixer at a ratio of 72.5% to 85.5%, 10% to 15%, 1.5% to 2.5%, 0.8% to 4.0% and 2.2% to 6.0% by mass as a mixed raw material for the durable layer;

[0018] Step (3), mixing the mixed raw materials of each layer in a planetary mixer, the mixing time is not less than 1 hour, and the mixing temperature is 70°C; the ingredients of each layer are respectively put into a twin-screw extruder for melt plasticization according to the mixing of the core layer and the surface layer, the screw diameter is 80 mm, the screw aspect ratio is 32, and the temperature is 260°C to 265°C;

[0019] Step (4), melt-extrude the melted and plasticized raw materials of each layer through a three-layer composite die (the die temperature is 260° C. to 280° C.), and cool them into cast sheets in a quenching roller. During the quenching process, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature is 33° C. to 37° C.;

[0020] Step (5), biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: preheating at 80°C to 90°C, stretching the sheet to a ratio of 1.2 to 1.5 at 80°C to 100°C, and cooling and shaping the sheet at 40°C to 60°C after longitudinal stretching; and transverse stretching after longitudinal stretching, wherein the transverse stretching conditions are: preheating at 90°C to 110°C, stretching the sheet to a ratio of 3.5 to 4.5 at 70°C to 90°C, and cooling and shaping the sheet at 80°C to obtain a durable and bump-resistant PETG heat shrinkable film.

[0021] Step (6), traction, reeling, slitting, packaging, and finished product.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) The shrink film prepared by the method of the present invention has a three-functional layer structure. The film as a whole can integrate the advantages of each functional layer. At the same time, the materials of each layer are derivatives of PET materials, with similar polarity, strong adhesion between the layers, and no stratification problem. It can reduce the difficulty of equipment operation, reduce the composite process, and reduce the overall thickness of the film, thereby reducing the production cost;

[0024] (2) The three-layer co-extruded film prepared by the method of the present invention has a surface layer mainly comprising a PET material with a high melt index modified by NPG, CHDM or NPG+CHDM monomers, which effectively reduces the crystallinity of the printed material, wherein the addition of a functional masterbatch is beneficial to increasing the roughness of the printed layer, which can effectively increase the corrosion and adhesion of the ink and improve the overall printability of the film;

[0025] (3) The method of the present invention adds a certain PET component to the core layer and the durable layer, combines the appropriate stretching ratio control in the stretching process and increases the film setting temperature, etc., to improve the film crystallinity to a certain extent while maintaining the good hand-jointing performance of the film, thereby effectively improving the overall tensile strength of the film. The toughening agent mainly improves the overall flexibility of the film in the core layer, and effectively increases the elongation of the film without reducing the strength of the film, so that the film exhibits the characteristics of both toughness and strength during use;

[0026] (4) The anti-scratch agent and lubricant added to the durable layer by the method of the present invention can strengthen the molecular arrangement of the polymer, strengthen the performance of the polymer, improve the hardness, and the additives migrate to the surface of the plastic to form a uniform particle dispersion, thereby improving the surface finish and scratch resistance of the product, while substantially not affecting the transparency of the product;

[0027] (5) The film of the present invention has a simple production process and has excellent bump and scratch resistance and strength properties. Products packaged with the film can maintain their beauty for a long time. DETAILED DESCRIPTION

[0028] The technical solution of the invention is further described below in conjunction with specific implementation methods. It should also be understood that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0029] The invention provides a durable and impact-resistant PETG heat shrinkable film, which comprises a printing layer, a core layer and a durable layer in sequence. When in use, the printing layer is on the inner side of a package; the printing layer mainly comprises NPG-modified PET and a functional masterbatch, and the main function of the printing layer is printability; the core layer mainly comprises PET, PETG and an impact-resistant toughening agent, and the main function of the core layer is to enable the film to have good shrinkage and elongation; the durable layer mainly comprises NPG-modified PET, PET, a scratch-resistant agent, a functional masterbatch and a lubricant, and the main functions of the durable layer are impact resistance and wear resistance. The mass percentage of NPG modified PET in the printing layer is 96.0% to 99.2%, and the mass percentage of functional masterbatch is 0.8% to 4.0%; in the core layer, the mass percentage of PETG is 60% to 75%, the mass percentage of anti-collision toughening agent is 5% to 15%, and the mass percentage of PET is 10% to 35%; in the durable layer, the mass percentage of NPG modified PET is 72.5% to 85.5%, the mass percentage of PET is 10% to 15%, the mass percentage of the anti-scratch agent is 1.5% to 2.5%, the mass percentage of functional masterbatch is 0.8% to 4.0%, and the mass percentage of lubricant is 2.2% to 6.0%.

[0030] Preferably, the PETG is S2012, Eastman GN071 or Eastman 0603.

[0031] Preferably, the PET is Sinopec Yizheng Chemical Fiber BG80, Sinopec Yizheng Chemical Fiber FG600 or Yuanhong Polymer YH600.

[0032] Furthermore, the scratch-resistant agent is transparent powder, nano zinc oxide or nano calcium carbonate.

[0033] Preferably, the functional masterbatch is compounded with erucamide and one or more of silicon dioxide, talc, clay, and kaolin.

[0034] Furthermore, the anti-collision toughening agent is POE-g-GMA (glycidyl methacrylate grafted polypropylene elastomer) or E-MA-GMA (terpolymer containing glycidyl methacrylate).

[0035] Furthermore, the lubricant is one or more of oleamide, erucamide, stearyl alcohol, pentaerythritol, and pentaerythritol stearate.

[0036] Preferably, the durable and impact-resistant PETG heat shrinkable film has a thickness of 30 to 100 μm.

[0037] Preferably, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0038] A method for preparing the above-mentioned durable and impact-resistant PETG heat shrinkable film comprises the following steps:

[0039] Step (1), drying the raw materials in a vacuum dryer to remove moisture;

[0040] Step (2), preliminarily mixing NPG modified PET and functional masterbatch in a mixer at a ratio of 96.0% to 99.2% and 0.8% to 4.0% by mass as a mixed raw material for the printing layer; preliminarily mixing PETG, a knock-resistant toughening agent and PET in a mixer at a ratio of 60% to 75%, 5% to 15% and 10% to 35% by mass as a mixed raw material for the core layer; preliminarily mixing NPG modified PET, PET, a scratch-resistant agent, a functional masterbatch and a lubricant in a mixer at a ratio of 72.5% to 85.5%, 10% to 15%, 1.5% to 2.5%, 0.8% to 4.0% and 2.2% to 6.0% by mass as a mixed raw material for the durable layer;

[0041] Step (3), mixing the mixed raw materials of each layer in a planetary mixer, the mixing time is not less than 1 hour, and the mixing temperature is 70°C; the ingredients of each layer are respectively put into a twin-screw extruder for melt plasticization according to the mixing of the core layer and the surface layer, the screw diameter is 80 mm, the screw aspect ratio is 32, and the temperature is 260°C to 265°C;

[0042] Step (4), melt-extrude the melted and plasticized raw materials of each layer through a three-layer composite die (the die temperature is 260° C. to 280° C.), and cool them into cast sheets in a quenching roller. During the quenching process, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature is 33° C. to 37° C.;

[0043] Step (5), biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: preheating at 80°C to 90°C, stretching the sheet to a ratio of 1.2 to 1.5 at 80°C to 100°C, and cooling and shaping the sheet at 40°C to 60°C after longitudinal stretching; and transverse stretching after longitudinal stretching, wherein the transverse stretching conditions are: preheating at 90°C to 110°C, stretching the sheet to a ratio of 3.5 to 4.5 at 70°C to 90°C, and cooling and shaping the sheet at 80°C to obtain a durable and bump-resistant PETG heat shrinkable film.

[0044] Step (6), traction, reeling, slitting, packaging, and finished product.

[0045] Example 1

[0046] (1) NPG modified PET (YH103, Yuanhong Polymer), PETG ( S2012), functional masterbatch and other raw materials are dried in a vacuum dryer to remove moisture;

[0047] (2) The printing layer, the core layer, and the durable layer are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0048] The printing layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 96.0%: 4.0%;

[0049] The core layer comprises the following components by mass percentage: PETG ( S2012): impact toughening agent (POE-g-GMA): PET (Sinopec Yizheng Chemical Fiber BG80) = 60%: 15%: 25%;

[0050] The durable layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (transparent powder): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (pentaerythritol stearate) = 72.5%: 15%: 2.5%: 4.0%: 6.0%;

[0051] (3) The ingredients of each layer are uniformly mixed in a planetary mixer for a mixing time of not less than 1 hour. The mixing temperature is controlled at 70°C. The ingredients are put into a twin-screw extruder for melt plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 260°C to 265°C;

[0052] (4) Melting and extruding the melted and plasticized raw materials of each layer through a three-layer composite die head at a die head temperature of 270° C.

[0053] (5) When the melt is extruded into a cast sheet, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature of the quenching roller is controlled at 33°C to 37°C.

[0054] (6) biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: single-point stretching by infrared heating, preheating at 85°C, stretching the sheet to a multiple of 1.5 at 90°C, and cooling and shaping at 50°C after longitudinal stretching; transverse stretching is performed after the longitudinal stretching, wherein the transverse stretching conditions are: preheating at 100°C, stretching the sheet to a multiple of 4.0 at 80°C, and cooling and shaping the sheet at 85°C after transverse stretching to obtain a durable and bump-resistant PETG heat shrinkable film;

[0055] Among them, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0056] Example 2

[0057] (1) Drying the raw materials such as NPG-modified PET (YH103, Yuanhong Polymer), PETG (Eastman GN071), and functional masterbatch in a vacuum dryer to remove moisture;

[0058] (2) The printing layer, the core layer, and the durable layer are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0059] The printing layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 99.2%: 0.8%;

[0060] The core layer comprises the following components by mass percentage: PETG ( S2012): anti-collision toughening agent (E-MA-EMA): PET (Sinopec Yizheng Chemical Fiber FG600) = 75%: 15%: 10%;

[0061] The durable layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (nano calcium carbonate): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (oleic acid amide) = 85.5%: 10%: 1.5%: 0.8%: 2.2%;

[0062] (3) The ingredients of each layer are uniformly mixed in a planetary mixer for a mixing time of not less than 1 hour. The mixing temperature is controlled at 70°C. The ingredients are put into a twin-screw extruder for melt plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 260°C to 265°C;

[0063] (4) Melting and extruding the melted and plasticized raw materials of each layer through a three-layer composite die head at a die head temperature of 270° C.

[0064] (5) When the melt is extruded into a cast sheet, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature of the quenching roller is controlled at 33°C to 37°C.

[0065] (6) biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: single-point stretching by infrared heating, preheating at 85°C, stretching the sheet to a multiple of 1.5 at 90°C, and cooling and shaping at 50°C after longitudinal stretching; transverse stretching is performed after the longitudinal stretching, wherein the transverse stretching conditions are: preheating at 100°C, stretching the sheet to a multiple of 4.0 at 80°C, and cooling and shaping the sheet at 85°C after transverse stretching to obtain a durable and bump-resistant PETG heat shrinkable film;

[0066] Among them, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0067] Example 3

[0068] (1) Drying the raw materials such as NPG-modified PET (YH103, Yuanhong Polymer), PETG (Eastman 0603), and functional masterbatch in a vacuum dryer to remove moisture;

[0069] (2) The printing layer, the core layer, and the durable layer are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0070] The printing layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 98.0%: 2.0%;

[0071] The core layer comprises the following components by mass percentage: PETG ( S2012): anti-collision toughening agent (POE-g-GMA): PET (Yuanhong Polymer YH600) = 60%: 5%: 35%;

[0072] The durable layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (nano zinc oxide): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (oleic acid amide) = 72.5%: 15%: 2.5%: 4.0%: 6.0%;

[0073] (3) The ingredients of each layer are uniformly mixed in a planetary mixer for a mixing time of not less than 1 hour. The mixing temperature is controlled at 70°C. The ingredients are put into a twin-screw extruder for melt plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 260°C to 265°C;

[0074] (4) Melting and extruding the melted and plasticized raw materials of each layer through a three-layer composite die head at a die head temperature of 270° C.

[0075] (5) When the melt is extruded into a cast sheet, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature of the quenching roller is controlled at 33°C to 37°C.

[0076] (6) biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: single-point stretching by infrared heating, preheating at 85°C, stretching the sheet to a multiple of 1.5 at 90°C, and cooling and shaping at 50°C after longitudinal stretching; transverse stretching is performed after the longitudinal stretching, wherein the transverse stretching conditions are: preheating at 100°C, stretching the sheet to a multiple of 4.0 at 80°C, and cooling and shaping the sheet at 85°C after transverse stretching to obtain a durable and bump-resistant PETG heat shrinkable film;

[0077] Among them, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0078] Example 4

[0079] (1) NPG modified PET (YH103, Yuanhong Polymer), PETG ( S2012), functional masterbatch and other raw materials are dried in a vacuum dryer to remove moisture;

[0080] (2) The printing layer, the core layer, and the durable layer are prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0081] The printing layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 98.8%: 1.2%;

[0082] The core layer comprises the following components by mass percentage: PETG ( S2012): impact toughening agent (POE-g-GMA): PET (Sinopec Yizheng Chemical Fiber BG80) = 70%: 12%: 18%;

[0083] The durable layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (transparent powder): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (oleic acid amide) = 78.0%: 12%: 2.0%: 2.8%: 5.2%;

[0084] (3) The ingredients of each layer are uniformly mixed in a planetary mixer for a mixing time of not less than 1 hour. The mixing temperature is controlled at 70°C. The ingredients are put into a twin-screw extruder for melt plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 260°C to 265°C;

[0085] (4) Melting and extruding the melted and plasticized raw materials of each layer through a three-layer composite die head at a die head temperature of 270° C.

[0086] (5) When the melt is extruded into a cast sheet, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature of the quenching roller is controlled at 33°C to 37°C.

[0087] (6) biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: single-point stretching by infrared heating, preheating at 85°C, stretching the sheet to a multiple of 1.5 at 90°C, and cooling and shaping at 50°C after longitudinal stretching; transverse stretching is performed after the longitudinal stretching, wherein the transverse stretching conditions are: preheating at 100°C, stretching the sheet to a multiple of 4.0 at 80°C, and cooling and shaping the sheet at 85°C after transverse stretching to obtain a durable and bump-resistant PETG heat shrinkable film;

[0088] Among them, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0089] Example 5

[0090] (1) NPG modified PET (YH103, Yuanhong Polymer), PETG ( S2012), functional masterbatch and other raw materials are dried in a vacuum dryer to remove moisture;

[0091] (2) Each layer of the ABC three-layer structure is prepared according to the composition ratio and preliminarily mixed in a mixer, wherein:

[0092] The printing layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 98.8%: 1.2%;

[0093] The core layer comprises the following components by mass percentage: PETG ( S2012): impact toughening agent (POE-g-GMA): PET (Sinopec Yizheng Chemical Fiber BG80) = 70%: 12%: 18%;

[0094] The durable layer comprises the following components by mass percentage: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (transparent powder): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (oleic acid amide) = 78.0%: 12%: 2.0%: 2.8%: 5.2%;

[0095] (3) The ingredients of each layer are uniformly mixed in a planetary mixer for a mixing time of not less than 1 hour. The mixing temperature is controlled at 70°C. The ingredients are put into a twin-screw extruder for melt plasticization. The screw diameter is selected to be 80 mm, the aspect ratio is 32, and the temperature is 260°C to 265°C;

[0096] (4) Melting and extruding the melted and plasticized raw materials of each layer through a three-layer composite die head at a die head temperature of 270° C.

[0097] (5) When the melt is extruded into a cast sheet, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature of the quenching roller is controlled at 33°C to 37°C.

[0098] (6) biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: single-point stretching by infrared heating, preheating at 85°C, stretching the sheet to a multiple of 1.5 at 90°C, and cooling and shaping at 50°C after longitudinal stretching; transverse stretching is performed after the longitudinal stretching, wherein the transverse stretching conditions are: preheating at 100°C, stretching the sheet to a multiple of 4.0 at 80°C, and cooling and shaping the sheet at 85°C after transverse stretching to obtain a durable and bump-resistant PETG heat shrinkable film;

[0099] Among them, the thickness ratio of the printing layer, the core layer and the durable layer is 10:60:30.

[0100] Comparative Example 1

[0101] The core layer in this comparative example contains the following components by mass percentage: PETG ( S2012): PET (Sinopec Yizheng Chemical Fiber BG80) = 82%: 18%; other layer components are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0102] Comparative Example 2

[0103] The core layer in this comparative example contains the following components by mass percentage: PETG ( S2012): impact-resistant toughening agent (POE-g-GMA) = 88%: 12%; other layer components are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0104] Comparative Example 3

[0105] The core layer in this comparative example contains the following components in percentage by mass: PET (Sinopec Yizheng Chemical Fiber BG80): impact-resistant toughening agent (POE-g-GMA) = 85%: 15%; the components of other layers are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0106] Comparative Example 4

[0107] The durable layer in this comparative example contains the following components in percentage by mass: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (transparent powder): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 83.2%: 12%: 2.0%: 2.8%, and the other layer components are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0108] Comparative Example 5

[0109] The durable layer in this comparative example contains the following components in percentage by mass: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (oleic acid amide) = 80.0%: 12%: 2.8%: 5.2%, and the other layer components are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0110] Comparative Example 6

[0111] The durable layer described in this comparative example contains the following components in percentage by mass: NPG modified PET (YH103, Yuanhong Polymer): PET (Sinopec Yizheng Chemical Fiber BG80): scratch resistant agent (transparent powder): lubricant (oleic acid amide) = 80.8%: 12%: 2.0%: 5.2%, and the components of other layers are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0112] Comparative Example 7

[0113] The durable layer described in this comparative example contains the following components in percentage by mass: NPG modified PET (YH103, Yuanhong Polymer): scratch resistant agent (transparent powder): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER): lubricant (oleic acid amide) = 90.0%: 2.0%: 2.8%: 5.2%, and the other layer components are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0114] Comparative Example 8

[0115] The durable layer described in this comparative example contains the following components in percentage by mass: NPG modified PET (YH103, Yuanhong Polymer): functional masterbatch (50% anti-blocking agent SiO2 and 50% slip agent crodamide ER) = 97.2%: 2.8%, and the other layer components are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0116] Comparative Example 9

[0117] In this embodiment, the cast sheet is stretched transversely, and the stretching conditions are adjusted to: the stretching ratio is 3.0. The components of each layer are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0118] Comparative Example 10

[0119] In this embodiment, the cast sheet is longitudinally stretched, and the stretching conditions are adjusted to: the stretching ratio is 1.0. The components of each layer are the same as those in Example 4, and the preparation method is consistent with that in Example 4.

[0120] Comparative Example 11

[0121] In this embodiment, the cast sheet is stretched transversely, and the stretching conditions are adjusted as follows: after preheating at 100°C, the stretching ratio is reached to 4.0 at 80°C; after transverse stretching, it is cooled and formed at 70°C; the components of each layer are the same as those in Example 4, and the preparation method is consistent with Example 4.

[0122] Comparative Example 12

[0123] In this embodiment, the cast sheet is stretched transversely, and the stretching conditions are adjusted as follows: after preheating at 100°C, the stretching ratio reaches 4.0 times at 80°C; after transverse stretching, it is cooled and formed at 100°C; the components of each layer are the same as those in Example 4, and the preparation method is consistent with Example 4.

[0124] The thickness, tensile strength, elongation at break, palm-jointing performance, anti-collision performance, shrinkage rate and haze of the durable and anti-collision PETG heat shrinkable films prepared in Examples 1 to 5 and Comparative Examples 1 to 12 were tested respectively, wherein the tensile strength and elongation at break were measured according to the GB / T 1040.3 method; the transmittance and haze were measured according to the GB / T 2410-2008 related methods; the method for testing the anti-collision performance is to shrink the film on the bottle, put it in the carton, shake it for 5 minutes, observe the scratches on the surface of the heat shrink film on the bottle, and record the number. A large number indicates poor anti-collision performance, otherwise it is good; the wear resistance test uses a certain method to rub the surface, and the instrument is used to measure the change in haze. The haze value is used as a comparison basis for the anti-wear effect. The method is as follows: after the sample film has been tested for haze, it is attached to the small steel door used for testing friction, placed on the smooth glass surface for testing, and a certain weight (2KG) is pressed on the weight, and pulled in the same direction 5 times, the sample film is taken down to test the haze of the middle part, and after measuring the haze, it is attached to the small door again, and the haze is measured 5 times in the above way. Record the haze (10 times in total), and then pull it 5 times to measure the haze for a total of 15 times. Record the value. Under the same test conditions, the haze value changes relatively small, and the anti-wear effect is relatively good. The test results are shown in Table 1.

[0125] Table 1 Performance of durable and impact-resistant PETG heat shrink film

[0126]

[0127] It can be seen from Table 1 that by comparing Examples 1 to 4 and Comparative Example 1, when the core layer uses (5% to 15%) of the anti-collision toughening agent (POE-g-GMA), its elongation at break increases, indicating that the overall toughness of the film is improved, which will reduce the number of scratches that are easily generated when the bottles collide with each other in a simulated transportation environment, thereby achieving the effect of improving the film's resistance to collision.

[0128] Compared with Comparative Examples 2 and 7, when PET is not added to the core layer and the durable layer, Example 4 has a higher elongation at break of the film, indicating better toughness, but its tensile strength is insufficient. When the film strength is insufficient, scratches are easily formed on the surface of the film, affecting the appearance of printing and other uses. The defects caused by scratches can easily lead to rupture of the film.

[0129] Compared with Comparative Example 3, when PETG is not added to the core layer of Example 4, the overall tensile strength of the film is greatly improved, but the elongation at break of the film is greatly reduced. The core layer mainly contains PET and a bump-resistant toughening agent. The film has too high crystallinity, causing the film to basically lose its heat shrinkage. In addition, the original haze of the film is too high, which is not conducive to printing (inside printing) and reduces the use effect of the film.

[0130] Compared with Comparative Examples 4, 5 and 6, when the durable layer does not contain any of the scratch resistant agent, lubricant or functional masterbatch, the haze of the film increases significantly after friction, indicating that the overall scratch and mar resistance of the film is poor, and cannot meet the requirements of durability and bump resistance of the film, affecting the packaging effect.

[0131] Compared with Comparative Example 8, when the durable layer does not contain the combination of PET, scratch resistant agent and lubricant, the haze of the film is greatly increased after friction, and the bump resistance of the film is greatly reduced after the simulated transportation test, which are both quite different from the embodiments.

[0132] Compared with Comparative Example 9, when the transverse stretching ratio in the process used in Example 4 is not appropriately selected, the crystalline orientation degree of the film is low, which may lead to insufficient overall strength of the film.

[0133] Compared with Example 10, when the process used in Example 4 does not perform longitudinal stretching and only uses 4 times transverse stretching, the transverse orientation degree and crystallinity of the film are too high, resulting in a slightly higher initial haze of the film and a weak six-ring palm-jointing of the film, which affects the use of the back-end palm-jointing agent overprinting.

[0134] In Example 4, compared with Comparative Examples 11 and 12, when the setting temperature in the transverse stretching process used is low (Comparative Example 11-70°C), the film crystallinity is low, and the bump and scratch resistance effects are average. When the setting temperature in the transverse stretching process used is high (Comparative Example 11-100°C), the film crystallizes excessively, resulting in a slightly higher initial haze of the film and a loose six-ring palm-joining of the film, which affects the use of the back-end palm-joining agent overprinting.

[0135] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A durable and impact-resistant PETG heat shrinkable film, comprising a printing layer, a core layer and a durable layer in sequence, characterized in that: The printing layer mainly includes NPG modified PET and functional masterbatch; the core layer mainly includes PET, PETG and a bump-resistant toughening agent, wherein the bump-resistant toughening agent is POE-g-GMA or E-MA-GMA; the durable layer mainly includes NPG modified PET, PET, a scratch-resistant agent, a functional masterbatch and a lubricant, wherein the scratch-resistant agent is transparent powder, nano zinc oxide or nano calcium carbonate, and the functional masterbatch is a compound of one or more of silicon dioxide, talcum powder, clay, and kaolin with erucic acid amide, and the lubricant is one or more of oleic acid amide, erucic acid amide, stearyl alcohol, pentaerythritol, and pentaerythritol stearate; the NPG in the printing layer The mass percentage of G-modified PET is 96.0%~99.2%, and the mass percentage of functional masterbatch is 0.8%~4.0%; the mass percentage of PETG in the core layer is 60%~75%, the mass percentage of anti-collision toughening agent is 5%~15%, and the mass percentage of PET is 10%~35%; the mass percentage of NPG-modified PET in the durable layer is 72.5%~85.5%, the mass percentage of PET is 10%~15%, the mass percentage of scratch-resistant agent is 1.5%~2.5%, the mass percentage of functional masterbatch is 0.8%~4.0%, and the mass percentage of lubricant is 2.2%~6.0%.

2. A durable and impact-resistant PETG heat shrinkable film as claimed in claim 1, characterized in that: The PETG is SKYGREEN® S2012, Eastman GN071 or Eastman 0603.

3. A durable and impact-resistant PETG heat shrinkable film as claimed in claim 1, characterized in that: The PET is Sinopec Yizheng Chemical Fiber BG80, Sinopec Yizheng Chemical Fiber FG600 or Yuanhong Polymer YH600.

4. A durable and impact-resistant PETG heat shrinkable film as claimed in claim 1, characterized in that: The thickness of the durable and impact-resistant PETG heat shrinkable film is 30-100 μm.

5. A durable and impact-resistant PETG heat shrinkable film as claimed in claim 1, characterized in that: The thickness ratio of the printing layer, the core layer and the durable layer is 10:60:

30.

6. A method for preparing the durable and impact-resistant PETG heat shrinkable film according to any one of claims 1 to 5, characterized in that: The following steps are included: Step (1), drying the raw materials in a vacuum dryer to remove moisture; Step (2), preliminarily mixing NPG modified PET and functional masterbatch in a mixer at a ratio of 96.0% to 99.2% and 0.8% to 4.0% by mass as a mixed raw material for the printing layer; preliminarily mixing PETG, anti-collision toughening agent and PET in a mixer at a ratio of 60% to 75%, 5% to 15% and 10% to 35% by mass as a mixed raw material for the core layer; preliminarily mixing NPG modified PET, PET, anti-scratch agent, functional masterbatch and lubricant in a mixer at a ratio of 72.5% to 85.5%, 10% to 15%, 1.5% to 2.5%, 0.8% to 4.0% and 2.2% to 6.0% by mass as a mixed raw material for the durable layer; Step (3), mixing the mixed raw materials of each layer in a planetary mixer, the mixing time is not less than 1 hour, and the mixing temperature is 70°C; the ingredients of each layer are respectively put into a twin-screw extruder for melt plasticization according to the mixing of the core layer and the surface layer, the screw diameter is 80 mm, the screw aspect ratio is 32, and the temperature is 260°C~265°C; Step (4), melt-extrude the melted and plasticized raw materials of each layer through a three-layer composite die head, and cool them into a casting sheet in a quenching roller. During the melt extrusion process, the die head temperature is 260°C to 280°C. During the quenching process, the ratio of the linear speed of the quenching roller to the melt outflow speed is controlled to be ≤5, and the temperature is 33°C to 37°C. Step (5), biaxially stretching the cast sheet, wherein the longitudinal stretching conditions are: preheating at 80°C to 90°C, stretching the sheet at a multiple of 1.2 to 1.5 at 80°C to 100°C, and cooling and shaping the sheet at 40°C to 60°C; after the longitudinal stretching, transverse stretching is performed, wherein the transverse stretching conditions are: preheating at 90°C to 110°C, stretching the sheet at a multiple of 3.5 to 4.5 at 70°C to 90°C, and cooling and shaping the sheet at 80°C to obtain a durable and bump-resistant PETG heat shrinkable film; Step (6), traction, winding, slitting, packaging, and finished product.

Citation Information

Patent Citations

  • PETG blow molding film and preparation method thereof

    CN101838445A

  • Thermoshrinkable polyester film and preparation method thereof

    CN102816417A